DALIA MOGAHED’S IDENTITY AS REFLECTED IN TED TALKS VIDEO - Zaenul Kurniawan Syahid (PARADIGM: Journal of Language and Literary Studies, 2018)
This study discussed the identity of Dalia Mogahed reflected through speech in an event called TED Talks. It is a big program have been featured great people around the world including Dalia Mogahed from various backgrounds to spread ideas. Her 2016 TED Talks entitled "What it's Like to be Muslim in America" was named one of the top TED Talks that year. This research employed a descriptive qualitative method as a research design since the purpose of the study is to provides a deep analysis of the data. The data collected through the transcription which is provided on the TED Talks official website. The finding revealed that Dalia Mogahed projected her social identity more dominant than role identity. There was no indication of the utterances that proved the characteristics of her personal identity. Therefore, the fluidity of identity was also shared by Mogahed in that situation to convince that identity was not fixed. It is highly recommended for further researchers who are interested in investigating the personal identity projection to follow up the findings of this research by concerning on finding someone’s personal identity in term of speech performance.